Development science modules interactive of shared type to increase reading interest and concept understanding - Permata Sari, Feby; Jumadi, Jumadi; Maryati, Maryati; Fahlevi, Aditya; Novia Dewi , Arina (Universitas Negeri Jakarta, 2024)
This research and development aims to produce shared-type interactive e-modules on energy sub-materials and energy sources. The e-module development model uses ADDIE by integrating energy transformation materials, energy applications in living things, as well as energy source-forming compounds. In field trials, using a type of pre-experiment research with a one-group pretest-posttest design. This research was carried out at SMPIT Bakti Insani class VII with saturated sampling technique. The data collection technique uses essay questions to find out the results of understanding the concept and a likert scale questionnaire to find out the results of reading interest. The data analysis technique uses a paired T test with the aim of seeing the significance of the e-module to reading interest and concept understanding and the n gain test to see an increase in the value of reading interest and concept understanding. Based on theoretical feasibility tests by experts, an average of 40.4 with excellent categories and empirical feasibility tests by students were 63.75 with excellent categories. Based on the development and research, it can be concluded that 1) the shared type interactive science e-module product is feasible to use with an excellent category; 2) the shared type interactive science e-module affects the interest in reading and understanding concepts with a significance of 0.000; 3) the shared-type interactive science e-module is able to increase reading interest by 0.52 with medium category and increase understanding of concepts 0.81 with high category.